Carboxytherapy Versus Skin Microneedling in Treatment of Atrophic Postacne Scars: A Comparative Clinical, Histopathological, and Histometrical Study. Issue 10 (October 2018) - Moftah, Noha H.; El Khayyat, Mohammad A.M.; Ragai, Maha H.; Alaa, Heba
Abstract : BACKGROUND: Acne scarring has been a challenge to treat. Microneedling gained popularity in treatment of such scars. Meanwhile, carboxytherapy (CXT) is considered a novel treatment modality for acne scars. OBJECTIVE: To evaluate efficacy of CXT versus microneedling in treatment of acne scars. METHODS AND MATERIALS: Thirty-two patients with atrophic acne scars received 6 sessions of microneedling and CXT on right and left sides of face, respectively. Clinical evaluation with histopathological and computerized morphometric analysis was performed at 2 months after treatment. RESULTS: After either microneedling or CXT, there was significant decrease of total acne scars and its 3 types separately (icepicks, boxcar, and rolling) ( p ⩽ .001). Comparing both sides of face, there was no significant difference regarding grading response and reduction percentage of total scars and its types ( p > .05). Histopathologically, there was an improvement of character and organization of collagen and elastic fibers in addition to significant increase in epidermal thickness on both sides of face, with no significant difference between them ( p > .05). CONCLUSION: Both CXT and microneedling are equally effective, tolerable, safe, and noninvasive treatment modalities of atrophic acne scars. Similar histopathological changes were observed after both modalities, helping in better understanding their action.